Inoculum Potential of Fusarium spp. Relates to Tillage and Straw Management in Norwegian Fields of Spring Oats - Hofgaard, Ingerd S.; Seehusen, Till; Aamot, Heidi U.; Riley, Hugh; Razzaghian, Jafar; Le, Vinh H.; Hjelkrem, Anne-Grete R.; Dill-Macky, Ruth; Brodal, Guro (Frontiers in Microbiology, 2016)
The increased occurrence of Fusarium-mycotoxins in Norwegian cereals over the last decade, is thought to be caused by increased inoculum resulting from more cereal residues at the soil surface as a result of reduced tillage practices. In addition, weather conditions have increasingly promoted inoculum development and infection by Fusarium species. The objective of this work was to elucidate the influence of different tillage regimes (autumn plowing; autumn harrowing; spring plowing; spring harrowing) on the inoculum potential (IP) and dispersal of Fusarium spp. in spring oats. Tillage trials were conducted at two different locations in southeast Norway from 2010 to 2012. Oat residues from the previous year’s crop were collected within a week after sowing for evaluation. IP was calculated as the percentage of residues infested with Fusarium spp. multiplied by the proportion of the soil surface covered with residues. F. avenaceum and F. graminearum were the most common Fusarium species recovered from oat residues. The IP of Fusarium spp. was significantly lower in plowed plots compared to those that were harrowed. Plowing in either the autumn or spring resulted in a low IP. Harrowing in autumn was more effective in reducing IP than the spring harrowing, and IP levels for the spring harrowed treatments were generally higher than all other tillage treatments examined. Surprisingly low levels of F. langsethiae were detected in the residues, although this species is a common pathogen of oat in Norway. The percentage of the residues infested with F. avenaceum, F. graminearum, F. culmorum and F. langsethiae generally related to the quantity of DNA of the respective Fusarium species determined using qPCR. Fusarium dispersal, quantified by quantitative PCR analysis of spore trap samples collected at and after heading, generally corresponded to IP. Fusarium dispersal was also observed to increase after rainy periods. Our findings are in line with the general understanding that plowing is a means to reduce the IP of Fusarium spp. in cereal fields. The main inoculum source for F. langsethiae remains unclear. Our results will be useful in the development of forecasting tools to calculate the risk of Fusarium in cereals.